Tortugas Hide a destination for birding advocates studying migratory birds - Garde, Sereena Angelique DS (College of Architecture, University of the Philippines Diliman, 2019)
Bird hides, often referred to simply as hides by birders, are actually animal shelters for observation. The Tortugas Hide, allows birding advocates to view or observe wildlife specifically birds at a relatively close distance. The development is located in one of the Philippine's known bird-watching area, Balanga Wetland and Nature Park which is situated in Barangay Tortugas, Balanga City in Bataan. In one of its articles entitled "Bird-watching can help boost ecotourism industry, says UN environment agency," UN News reported that "bird-watching, a popular hobby around the world, can present significant economic opportunities for countries through sustainable tourism, the United Nations environment agency said today, stressing that States should increase efforts to support this growing industry." (United Nations, 2012). Birding activities (bird-watching, photography, and ornithological research) are given focus in other countries; however, it has not been given much attention in the Philippines. Having rich biodiversity and numerous bird-watching sites for migratory birds, the Philippines has great potential to become a world-renowned spot for avian observatories. The proper care and management of these bird-watching sites will not only benefit migratory birds but the ecosystem and human inhabitants as well. Balanga Wetland and Nature Park is one of the hotspots of migratory species in the country but the lack of facilities and proper management caused the drop in visiting tourists. The proposal of a bird-friendly research facility in the chosen site promotes the conservation of the environment, the rich migratory bird population of Balanga City, as well as the increase in the interest of birding advocates in observing, monitoring, picture taking, and studying the aforementioned species. Having proposed the development of a facility in a conservation site, a list of guidelines, design concepts, preferences, and limitations (gathered from interviews and references) must be taken into consideration to minimize any possible disruption by the structure to the natural processes or routines of the environment.